Epideictic rhetoric and sculptural complex of the Well of Moses - Mariano, Paloma Lima Santos (Revista de História, 2011)
The purpose of this article is to analyze the use of strategies originating in the genre of epideictic rhetoric in Claus Sluter’s Well of Moses in the Charterhouse of Champmol, in Dijon, dated around 1400. It will be argued that the Well is the work of an artist that makes ample use of rhetorical strategies, resorting to ornament and adornment, using art as a form of discourse.